The challenges of new Regional Basic Observation Network on the Regional Association III - Chira La Rosa, Jorge (2018)
According to decision 21 taken by 69th Executive Congress of World Meteorological Organization (WMO), the new Regional Basic Observations Network (RBON) will be created, which will be mainly made up of the Regional Basic Synoptic Network (RBSN) and Regional Basic Climatological Network (RBCN), but with new functions. It is expected that this new network will provide better services and It will allow regional observing capabilities to be fully exploited. However, although the RBSN and RBCN on the Regional Association III (RA III) have improved their performance with respect to previous years, there are still some challenges for the National Meteorological and Hydrological Weather Services (NMHSs) that must be solved in order that the RBON meets the expected objectives. In some NMHSs of the RA III, as in the case of Peru, there are institutions linked to the aeronautical sector whose interests currently are not necessarily aligned with the plans of NMHSs and WMO and those that have allowed in the past the conformation of the RBSN and RBCN networks with stations of their own networks. This coupled with the lack of WIGOS Regional Center that help to implement WIGOS National Plan, makes the implementation of the future Regional Basic Observations Network a challenge for these NMHSs. This presentation attempts to draw some of the key issues and to give some suggestions for the future development of RBON in the RA III.